PENGARUH PENGETAHUAN DAN MOTVASI LINGKUNGAN TERHADAP PERILAKU BERTANGGUNGJAWAB SISWA - niko bayu kumoro aji; Nadiroh Nadiroh; Samadi Samadi (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2019)
The HOTS questions are able to train students to think creatively, critic and innovative. Theobjectives of this research is try to finding out the information about the effect of academicbackground of students on the ability of high-level thinking (HOTS) in the environment. An ex postfacto method has been applied by involving n= 120 students at SMA Negeri 21 Jakarta. Data wasanalyzed by Paired Sample T-tes. The results revealed that there were significant differences ofstudent’s HOTS who come from academic background of MIA (Mathematics of Natural Sciences)and the academic background of IIS (Social Sciences). Therefore, to be considered aboutacademic background factors that can lead students to improve HOTS in the environment.Furtherresearch on other variables that can influence HOTS in the environment, the background ofrespondents not only on the students but can be done to the general public because the environmentto be the obligation of all the inhabitants of the earth.Environment has become the dominant issue inthe beginning of this century, we need to re-educate our thinking, with further possibility to rekindleour hope of a future with dignity for all. Therefore, to improve HOTS on the environment needs to beconsidered about the academic background. Learning in schools must be able to facilitate studentsin improving their thinking skills in order to create wise behavior towards the environment.